Management of Village-Owned Enterprises (BUMDES) to Increase Village Original Income (Case Study in Oemolo Village, East Amabi Oefeto Sub-District, Kupang Regency) - Yohanes Handrianus Laka (IRDH International Journal of Social Sciences & Humanities, 2025)
Village-owned enterprises (BUMDes) are village business institutions managed by the Community and Village Government in an effort to strengthen the Village economy. They are formed based on the village's needs and potential. “To increase Village Original Income (PADesa). BUMDes must be different from economic institutions in general. Inactive BUMDes are caused by various things, such as businesses that are not running and others. as mandated by the mandate of Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises and Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration Number 3 of 2021 concerning registration, data collection, ranking, guidance and development, procurement of goods or services for BUMDes together. The purpose of this research is to find out the development of BUMDES in Oemolo Village. The research used is a qualitative approach, with a case study research type on the BUMDes program in Oemolo Village. The role of BUMDes is more focused on empowerment. Thus, the focus of the research consists of fulfilling basic needs, access to public services, being able to actively participate, awareness of oneself and the environment's strengths and weaknesses, and the ability to control oneself and the environment. BUMDes Manekan has made most of the efforts to improve the community's economy, such as providing business capital, but it is still constrained in its stalled development. BUMDes management does not consider community readiness